Subducted Lithosphere Under South America From Multifrequency P Wave Tomography. Issue 6 (31st May 2021) - Mohammadzaheri, Afsaneh; Sigloch, Karin; Hosseini, Kasra; Mihalynuk, Mitchell G.
Abstract: We analyze mantle structure under South America in the DETOX‐P1 seismic tomography model, a global‐scale, multifrequency inversion of teleseismic P waves. DETOX‐P1 inverts the most extensive data set of broadband, waveform‐based traveltime measurements to date, complemented by analyst‐picked traveltimes from the ISC‐EHB catalog. The mantle under South America is sampled by ∼665, 000 cross‐correlation traveltimes measured on 529 South American broadband stations and on 5, 389 stations elsewhere. By their locations, depths, and geometries, we distinguish four high‐velocity provinces under South America, interpreted as subducted lithosphere ("slabs"). The deepest (∼1, 800–1, 200 km depth) and shallowest (<600 km) slab provinces are observed beneath the Andean Cordillera near the continent's northwest coast. At intermediate depths (1, 200–900 km, 900–600 km), two slab provinces are observed farther east, under Brazil, Bolivia and Venezuela, with links to the Caribbean. We interpret the slabs relative to South America's paleo‐position over time, exploring the hypothesis that slabs sank essentially vertically after widening by viscous deformation in the mantle transition zone. The shallowest slab province carries the geometric imprint of the continental margin and represents ocean‐beneath‐continent subduction during Cenozoic times. The deepest, farthest west slab complex formed under intra‐oceanic trenches during late Jurassic and Cretaceous times, far west of South America's paleo‐position adjoined to Africa. The two intermediate slab complexes record the Cretaceous transition from westward intra‐oceanic subduction to eastward subduction beneath South America. This geophysical inference matches geologic records of the transition from Jura‐Cretaceous, extensional "intra‐arc" basins to basin inversion and onset of the modern Andean arc ∼85 Ma. Plain Language Summary: Eastward subduction of the Pacific basin lithosphere beneath South America has generated arc magmatism and produced the modern Andes. However, extrapolation of the modern east‐dipping subduction scenario to before the Late Cretaceous does not readily explain the contrasting history of the ancestral Andes. Subducted former seafloor continues to exist in the mantle and remains visible to seismic tomography because P waves travel faster in it than in ambient mantle. We analyze such seismically fast domains, that is, "slabs" of interpreted paleo‐seafloor, at depths of ∼300–1, 800 km in our global tomography model DETOX‐P1. Combining these observations with quantitative plate reconstructions and geological observations, we attempt to reconstruct the subduction history under South America. The slab that dips eastward down beneath the present‐day Andes is relatively continuous to ∼900 km depth. Deeper down, slab geometries completely change. Voluminous slabs are unexpectedly imaged thousands of kilometers west of South America's reconstructed paleo‐margin. We argue that in the simplest explanation all slabs sank essentially in place, and a trans‐American, tectonic reconfiguration occurred the time equivalent to 900 km slab depth (∼80–90 Ma). Prior to this time, the "Andean" trench sat offshore (and the margin extended) but the subduction direction must have been oceanward, rather than eastward. Key Points: Global‐scale teleseismic P wave tomography model DETOX‐P1 is analyzed under South America The shallowest and the deepest slabs are found under (north)west South America, while intermediate‐depth slabs are found farther east If slabs sank roughly vertically, they initially formed under intra‐oceanic trenches, up until Late Cretaceous times